Extracorporeal shock wave treatment can selectively destroy end plates in neuromuscular junctions. Issue 3 (8th August 2017) - Kenmoku, Tomonori; Nemoto, Noriko; Iwakura, Nahoko; Ochiai, Nobuyasu; Uchida, Kentaro; Saisu, Takashi; Ohtori, Seiji; Nakagawa, Koichi; Sasho, Takahisa; Takaso, Masashi
ABSTRACT: Introduction: This study assesses the effect of radial extracorporeal shock wave (rESW) exposure on neuromuscular transmission and neuromuscular junction (NMJ) morphology. Methods: We applied 2, 000 rESWs at 0.18 mJ/mm 2 and a frequency of 15 Hz to the right calf of male rats, measured the compound muscle action potential (CMAP), and examined NMJ morphology using electron microscopy. Left calf muscles were used as controls. Results: rESW exposure significantly reduced CMAP amplitude without delayed latency in exposed muscles compared with controls. All rESW‐exposed muscles exhibited NMJs with irregular end plates. Mean interjunctional fold interval was significantly increased compared with controls. However, axon terminals and muscle fibers surrounding NMJs with irregular end plates were unchanged. Discussion: This localized destruction of end plates may be caused by differences in acoustic impedance induced by the density of acetylcholine receptors. These results provide a possible mechanism for the effectiveness of rESW treatment for spasticity and dystonia. Muscle Nerve 57 : 466–472, 2018